How strong is your firm's competitive advantage? - Marburger, Daniel R. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Perhaps the most confounding characteristic of the competitive marketplace is that everyone wants a piece of the action. If a firm successfully enters a new market, creates a new product, or designs new innovations for an existing product, it's just a matter of time before competitors follow suit. And the influx of competition inevitably places downward pressure on both price and profitability. But the speed at which competitors invade one's market is not the same in all industries; some are more resistant to the forces of competition than others. In 1979, Harvard economist Michael Porter theorized his Five Forces Model (updated in 2008). The Five Forces Model identifies the characteristics that can help insulate a firm from competitive forces. For the firm that seeks to put together a business plan, or for the firm that is considering opportunities for diversification, an understanding of the Five Forces Model is essential.
Part I. If you could choose any price, what would it be? Fundamentals for the single price firm -- 1. Economics and the business manager: what is economics all about? -- 2. The shareholders want their profits, and they want them now: short-run profit maximization for the firm -- Part II. What does five forces model say about your firm? -- 3. Warning: cheaper substitutes are hazardous to your profits -- 4. We could make more money if our competitors would just go away -- 5. Is my supplier holding five aces? The bargaining power of suppliers -- 6. When the buyer holds six aces: the bargaining power of buyers -- 7. How to keep firms from beating each other up -- Appendix I. How strong is your firm's competitive advantage? Summary of factors and strategies -- Appendix II. Relevant published case studies -- Notes -- References -- Index.
Includes bibliographical references (pages 131-140) and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF title page (viewed on November 25, 2015).
Keywords: Competition; Market share; Porter's Five Forces; bargaining power; market power; market barriers; product differentiation; product substitution; switching costs